Problems of revitalization of residential quarters of prefabricated buildings on the basis of Stanislaw Moniuszko quarter in Lublin - Ostańska, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
The author’s algorithm for designing revitalization programmes for housing estates of precast concrete buildings comprises consecutive steps of analyses and actions necessary for addressing the complex problems of the estates in full. The algorithm proposed by the author has been created for a particular estate, however, it is of general character. Its systematic approach allows the user to adapt it to other types of building stock, post-industrial conversions, traditional housing etc. assuming that their individual qualities are accounted for in the diagnosis.